Exo- and Endo-cannabinoids in Depressive and Suicidal Behaviors - Mannekote Thippaiah, Srinagesh; Iyengar, Sloka S.; Vinod, K. Yaragudri (Frontiers in Psychiatry, 2021)
Cannabis (marijuana) has been known to humans for thousands of years but its neurophysiological effects were sparsely understood until recently. Preclinical and clinical studies in the past two decades have indisputably supported the clinical proposition that the endocannabinoid system plays an important role in the etiopathogeneses of many neuropsychiatric disorders, including mood and addictive disorders. In this review, we discuss the existing knowledge of exo- and endocannabinoids, and the role of the endocannabinoid system in depressive and suicidal behavior. A dysfunction in this system, located in the brain regions such as the prefrontal cortex and limbic structures is implicated in mood regulation, impulsivity, and decision-making, and may increase the risk of negative mood and cognition, and suicidality. The literature discussed here also suggests that the endocannabinoid system may be a viable target for treatments for these neuropsychiatric conditions.